Nuevos emprendimientos y posibilidades de éxito, una perspectiva desde la ubicación geográfica que seleccionan los emprendedores de la ciudad de Riobamba-Ecuador. - López Lara, Juan Ignacio (2020)
The present research work is the result of an orderly and systematic methodological process, considering the problem of Riobamba city which, like many cities of Ecuador, the commercial activity is located in the center of them, this causes that the opportunities and success be limited only to traders who are in the urban area, specifically on the main streets,nearby the markets ,in the pantry centers and the bus terminals; which has led to the fact that the possibilities of success of new entrepreneurships are limited to their location and not to the characteristics of their business, the quality of their product or service and the effort that the entrepreneur gives to their business, becoming the research problem. How could new entrepreneurs improve their chances of success by placing themselves in spaces other than traditional ones in Riobamba city? Defining the objective of the present research in designing strategies for increasing the chances of success of supply-shop entrepreneurs in Riobamba city. To achieve the objective, the design of the methodology was carried out, being the mixed approach, the descriptive level and the deductive method, the field observation and the survey were used as techniques by means of two instruments: the observation sheet and questionnaire, (which were two: one aimed at entrepreneurs and the other at consumers of grocery stores). The results of the research show that the location of supply businesses is decisive to their success; Therefore, a proposal of strategies was developed to increase the possibilities of success of the grocery stores entrepreneurs in Riobamba city, which contains important elements such as the location of the business, the customers, the price and the competition